The potential of high resolution palaeoclimate reconstruction from Arctica islandica - Foster, Laura (University of St Andrews, 2008)
The potential of Arctica islandica, a long lived marine bivalve with a lifespan of over 300 years, to reconstruct a high resolution (sub-annual) climate record is explored in this thesis. Fluctuations in trace element and isotopic data from live-collected specimens from Irvine Bay, NW Scotland are compared to instrumental (particularly temperature) data. X-ray absorption spectroscopy data demonstrate the coordination state of Sr and Mg within the shell. These are consistent with models in which Sr substitutes ideally for Ca in aragonite, and Mg is bound predominantly to organic molecules. Sr/Ca incorporation may be influenced by changes in the crystal nucleation, propagation and growth rate as well as vital effects. However any effect of seawater temperature on Sr/Ca incorporation was obscured by these other factors. Mg concentration is not a linear function of a single environmental variable or organic content within the shell, indicating that Mg uptake is biologically mediated. Ba variation shows sporadic increases (of >500% above baseline) in both shells, the timing of which is similar between the prismatic layer and umbo region. The maxima are, however, not synchronous between the two shells analysed. The controls on Ba uptake require further research, but low Ba/Ca may reflect Ba/Ca concentrations within the seawater. Aliquots taken from cod otoliths show that micromilling has negligible effect on δ¹⁸O. The range of reconstructed temperature from δ¹⁸O profiles Arctica islandica shows good agreement with the sea surface temperature data from the nearby Millport marine station to within 2.1 °C. However, both the interannual and intra-annual variation appears to be sensitive to changes in temporal resolution resulting from changes in growth rates. Modelling of δ¹⁸O highlights dependence on changes in temporal resolution of the sampling, in addition to temperature and salinity. Results from the radiocarbon pilot study show that Arctica islandica is a suitable archive for changes in radiocarbon associated ...